A two-stage MCDM model for reverse logistics network design of waste batteries in Turkey - KILIÇ, HÜSEYİN SELÇUK; KALENDER, ZEYNEP TUĞÇE (My University, 2023)
Inadequate environmental resources and overpopulation reveal the need to protect and recover natural resources attentively. In this sense, the reverse logistics concept emerged as a key solution since it deals with product flow from the final user to the origin. There are various items that need to be considered in well-planned reverse logistics network designs and one of these items is batteries which include hazardous and precious materials in it. Hence, waste management of batteries via recycling becomes a very significant issue from both economic and environmental benefits. Accordingly, depending on the importance of the topic, a two-stage methodology is proposed in this study for providing a network design under multiple objectives. Within the first stage, the importance weights of objectives are obtained via Spherical Fuzzy Analytical Hierarchy Process (SF-AHP) and they are found as 0.248 for cost minimization, 0.3 for carbon emission minimization, 0.256 for employment rate maximization and 0.196 for development rate maximization. Afterward, in the second stage, a Multi-Objective Mixed Integer Linear Programming Model (MO-MILP) is developed to design the reverse logistics network and an application is performed in Turkey for validation. The model is solved for various scenarios including different quantities to be collected. Hence, it is obtained that the satisfaction degrees for employment and development objectives are 100% in all of the scenarios. However, the satisfaction degree of carbon emission minimization is around 96% and the less satisfied objective is the cost minimization having a satisfaction degree of 75% on average.
Keywords: Bilgisayar Bilimleri; Veritabanı ve Veri Yapıları; Mühendislik ve Teknoloji; Computer Sciences; Database and Data Structures; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; BİLGİSAYAR BİLİMİ, YAZILIM MÜHENDİSLİĞİ; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; COMPUTER SCIENCE, SOFTWARE ENGINEERING; Yazılım; Fizik Bilimleri; Software; Physical Sciences; MCDM; Network design; Recycling; Reverse logistics; SF-AHP; Waste batteries